2023
DOI: 10.1111/imb.12829
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of CYP9A9 increases the susceptibility to lufenuron, methoxyfenozide and a mixture of both in Spodoptera exigua

Abstract: Lufenuron (LUF) and Methoxyfenozide (MET) as Insect Growth Regulators (IGRs) contribute to the current control of the catastrophic crop pest, Spodoptera exigua (Lepidoptera, Noctuidae). Yet S. exigua has evolved resistance to LUF and MET, which is possibly mediated by cytochrome P450 monooxygenases (P450s), particularly from the CYP3 clade family, as it plays a key role in the detoxification of insecticides. However, a mixture of LUF and MET (MML) (optimal ratio: 6:4) remains highly insecticidal. Here, we anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Mammalian studies have shown similar results with increased expression of CYP3A protein after diflubenzuron exposure (Dubois et al, 1996;Sapone et al, 2005). In insects, biotransformation of lufenuron depends on CYP9 and CYP12 proteins (Bogwitz et al, 2005;Zhang et al, 2023), CYP families that belong to the mammalian CYP3 and CYP5 families.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Mammalian studies have shown similar results with increased expression of CYP3A protein after diflubenzuron exposure (Dubois et al, 1996;Sapone et al, 2005). In insects, biotransformation of lufenuron depends on CYP9 and CYP12 proteins (Bogwitz et al, 2005;Zhang et al, 2023), CYP families that belong to the mammalian CYP3 and CYP5 families.…”
Section: Discussionmentioning
confidence: 77%
“…Mammalian studies have shown similar results with increased expression of CYP3A protein after diflubenzuron exposure (Dubois et al., 1996; Sapone et al., 2005). In insects, biotransformation of lufenuron depends on CYP9 and CYP12 proteins (Bogwitz et al., 2005; Zhang et al., 2023), CYP families that belong to the mammalian CYP3 and CYP5 families. Although CYP3A appears to be involved in the detoxification of benzoylurea insecticides in vertebrates, this gene was not differentially regulated in this study ( cyp3a27 was 1.4‐fold upregulated at day 14 ( p ‐value = .03, p ‐adj = .22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the diverse genetic options for insecticide resistance evolution caused by the amplification of P450s, the involvement of P450 gene overexpression in xenobiotic detoxification has been widely studied. , CYP6DP genes in Trialeurodes vaporariorum and Bemisia tabaci showed a strongly transcriptional response to nicotine, and several CYP6DP genes were found to be related to imidacloprid resistance . Inducible CYP9A9 of Spodoptera exigua was verified to participate in lufenuron and methoxyfenozide detoxification by using RNAi S.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays a large number of P450 genes have been reported to be related to insect resistance. For example, the overexpression of CYP6B7 , CYP6B6 , CYP6B2 , CYP337B3 , CYP332A1 , and CYP6AE11 was associated with pyrethroids resistance in H. armigera . Overexpression of P450 genes was also related to the resistance of other insects, such as Plutella xylostella , Spodoptera exigua , Tribolium castaneum , and Aphis gossypii . Gene expression in insects is sophisticated and involves in the process of transcription, while transcription factors are able to intricately regulate the transcription of many functional genes that respond to external environmental stresses including insecticides .…”
Section: Introductionmentioning
confidence: 99%